Manfaat Kanopi Pohon dalam Mereduksi Aliran Permukaan Studi Kasus: Sempadan Sungai Ciliwung Tengah, Kota Bogor - NUGROHO, FLORENTHIUS AGUNG; FATIMAH, INDUNG SITTI (Jurnal Arsitektur Lansekap; Vol.2, No.2, Oktober 2016DO - 10.24843/JAL.2016.v02.i02.p10, 2016)
ABSTRACT The Benefit of Trees Canopy in Reducing RunoffCase Study: Border of Center Ciliwung River, Bogor Municipality Bogor as one of Center Ciliwung Sub Region River flow has decreased the percentage of green open space from year to year (Bappeda 2007). Study area boundary is the border as far as 300 meters to the left and right side of Ciliwung River. The method of this research is to estimating the benefits of tree canopy using Quickbird satellite image of the city of Bogor in 2006 with the software ArcView GIS 3.2 extensions CITYgreen 5.4. The study includes comparisons between the percentage of built up area and green open space. Comparison of built up area and the largest area of green open space can be found in Tanah Sareal District, the ratio reached 2:1. While the smallest ratio can be found in the MiddleDistrict of Bogor (1:1). This means the ideal condition of river’s border are found in the Middle District of Bogor that can decreasing runoff well. The estimation of trees canopy benefits can be seen from the amount of runoff volume, it can be predicted that trees canopy in study area can reduce average ± 7,55% of runoff volume. This means that the conditions in the study area was still below the average standard riverine.